PENINGKATAN HASIL BELAJAR DENGAN MODEL PROJECT BASED LEARNING (PJBL) - Jelita Panjaitan (Lembaga Penenlitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2019)
This study aims at analyzing whether student learning outcomes taught with the PjBL model are better than direct instruction models, analyzing whether student learning outcomes those who have a scientific attitude above the average are better, analyzing whether there is an interaction between the PjBL model based on the collaborative and the students’ learning outcomes. This study is a quasi-experimental study with two group pre-test and post-test designs. The population of this study is all first semester students of Physics Education Study Program in Academic Year 2018/2019, Faculty of Teacher Training and Education, Darma Agung University, Medan. The sample in this study was taken by cluster random sampling, namely as many as 2 classes totaling 40 people in which class X-1 as an experimental class taught with a collaborative-based PjBL model consisting of 32 students, class X-2 as a control class taught with the direct instruction model consisting of 20 students.The instrument of this study used a learning essay test consisting of 10 questions in the form of a questionnaire consisting of 10 cases and has been declared valid and reliable. The resulting data was analyzed by using two-way ANAVA. The results of the study showthat the students’ learning outcomes taught by the collaborative PjBL model are better than the direct instruction model, the learning outcomes of students who have a scientific attitude above average are better than students who have a scientific attitude below the average. There is an interaction between the collaborative based PjBL model and the direct model of student learning outcomes.